Hadith and the Formation of Noble Morals: A Thematic Analysis and Its Relevance to the National Curriculum - Hibroni Arifandy; Ahmad Muhammad Tidjani; Abdul Kirom (Penerbit Presisi Pustaka, 2026)
The phenomenon of moral degradation in the modern era is rampant, marked by increasing violence, intolerance, and weakening social ethics among students. This condition shows a gap between technological advancement and character building, thus requiring a strong and authentic foundation of values. This study aims to provide a conceptual contribution to the integration of hadith values into the national education system. It uses a qualitative method with a literature study approach involving analysis of hadith books, moral literature, and scientific research related to character education. The analysis procedure includes data reduction, presentation of data in the form of thematic narratives, and drawing conclusions through the integration of various sources with triangulation to maintain validity. The results of the study show that the Prophet's hadiths contain fundamental moral values such as honesty, trustworthiness, compassion, responsibility, and discipline, which serve as pillars of character building. Hadiths about the importance of morals and seeking knowledge form the philosophical basis for moral and spiritual education. Their implementation is evident in the exemplary behavior of teachers, student manners, the instilling of values, and the integration of prophetic values into learning practices. In addition, the values of the hadiths are proven to be relevant and in line with the six dimensions of the Pancasila Student Profile, especially in the aspects of faith, piety, noble character, mutual cooperation, and independence. Overall, this research emphasizes the importance of revitalizing character education through the integration of hadith values into the national curriculum in order to shape a generation that is moral, adaptive, and morally and intellectually superior.